Flexible composite mechanical energy harvester from a ferroelectric organoamino phosphonium salt - Vijayakanth, Thangavel; Srivastava, Anant Kumar; Ram, Farsa; Kulkarni, Priyangi; Shanmuganathan, Kadhiravan; Praveenkumar, Balu; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2018)
A new binary organic salt diphenyl diisopropylamino phosphonium hexaflurophosphate (DPDPPF6) was shown to exhibit a good ferroelectric response and employed for mechanical energy harvesting application. The phosphonium salt crystallizes in the monoclinic noncentrosymmetric space group Cc and exhibits an H-bonded 1D chain structure due to N-HF interactions. Ferroelectric measurements on the single crystals of DPDPPF6 gave a well-saturated rectangular hysteresis loop with a remnant (P-r) polarization value of 6Ccm(-2). Further, composite devices based on polydimethylsiloxane (PDMS) films for various weight percentages (3, 5, 7, 10 and 20wt%) of DPDPPF6 were prepared and examined for power generation by using an impact test setup. A maximum output peak-to-peak voltage (V-PP) of 8.5V and an output peak-to-peak current (I-PP) of 0.5A was obtained for the non-poled composite film with 10wt% of DPDPPF6. These results show the efficacy of organic ferroelectric substances as potential micropower generators.
Keywords: binary phosphonium salts; energy conversion; ferroelectricity; hydrogen bonding; polymer composites

Imido-P(V) trianion supported enantiopure neutral tetrahedral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Paithankar, Harshad; Chugh, Jeetender; Steiner, Alexander; Boomishankar, Ramamoorthy (Chemical Communications, 2018)
Charge-neutral chiral hosts are attractive due to their ability to recognize a wide range of guest functionalities and support enantio-selective processes. However, reports on such charge-neutral cages are very scarce in the literature. Here, we report an enantiomeric pair of tetrahedral Pd(II) cages built from chiral tris(imido) phosphate trianions and oxalate linkers, which exhibit enantioselective separation capabilities for epichlorohydrin, beta-butyrolactone, and 3-methyl- and 3-ethyl cyclopentanone.

All-organic composites of ferro- and piezoelectric phosphonium salts for mechanical energy harvesting application - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry of Materials, 2019)
Molecular ferroelectrics owing to their lightweight, flexibility, and phase stability are drawing attention in the fields of flexible electronics, optical devices, and energy materials. In this paper, we report a series of binary organoamino phosphonium salts containing triphenyl isopropylaminophosphonium (TPAP), diphenyl diisopropylaminophosphonium (DPDP), phenyl triisopropylaminophosphonium (PTAP), and tetraisopropylaminophosphonium (TIAP) cations supported by lower symmetric tetrahedral BF4-, ClO4-, and IO4- anions. The P-E hysteresis loop measurements on these polar organic salts gave high remnant polarization (P-r) values of 35.36, 21.83, and 21.12 mu C cm(-2) for the DPDP center dot BF4, DPDP center dot ClO4, and DPDP center dot IO4 salts, respectively, having 1D hydrogen-bonded chain structures built from strong N-H center dot center dot center dot X (X = F or 0) interactions. For the first time, highly flexible composite devices have been prepared for the piezoelectric salts TPAP center dot BF4, DPDP center dot BF4, and TIAR center dot BF4 using thermoplastic polyurethane (TPU) as the matrix. The observed maximum peak-to-peak output voltages (V-pp) for the 10 wt % composite devices of TPAP center dot BF4/TPU, DPDP center dot BF4/TPU, and TIAP center dot BF4/TPU are found to be 7.37, 8.95, and 4.75 V, respectively. These composite devices exhibit excellent durability, cycling stability, and viscoelastic properties. They also show the capacitor charging capabilities reaching their maximum charging points within 60 s.

Chiral separation of styrene oxides supported by enantiomeric tetrahedral neutral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Ferrara, Joseph D.; Del Campo, Mark; Le Magueres, Pierre; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2019)
The separation of enantiomers is of considerable importance in the preparation of the compounds of biological interests, catalysis, and drug development. Here, we report a novel enantioseparation of styrene epoxides (SOs) resolved in the presence of a pair of enantio-enriched tetrahedral cages. Chiral neutral cages of formula [(Pd3X*)(4)(C6O4Cl2)(6)] ([X*](3-) = RRR-or SSS-[PO(N(*CH(CH3)Ph)(3)](3)) are constructed from Pcl, building units supported by tris(imido)phosphate trianions and chloranilate linkers. These cages exhibit considerable enantioselective separation capabilities toward a series of styrene epoxides via a crystallization inclusion method. A highest enantiomeric excess (ee) value of up to 80% is achieved for the (R)-4-fluorostyrene oxide.

Nanocellulose reinforced flexible composite nanogenerators with enhanced vibrational energy harvesting and sensing properties - Ram, Farsa; Gudadhe, Aniket; Vijayakanth, Thangavel; Aherrao, Swapnil; Borkar, Vivek; Boomishankar, Ramamoorthy; Shanmuganathan, Kadhiravan (2020)
We report here enhanced vibration and pressure sensing properties of nanocellulose reinforced flexible composite piezoelectric nanogenerators (PENGs). Surface fluorinated nanocellulose crystals (FNC) were incorporated into poly(vinylidene fluoride) (PVDF) and electrospun into composite nanofibers. Incorporation of only 2 wt % FNC in PVDF resulted in a significant enhancement in pressure sensitivity with a very low detectable pressure limit of 10 Pa and a sensitivity of up to 18 mV/kPa. The composite PENGs also demonstrated very high sensitivity for forced continuous vibrations. 2FNC/PVDF composites resulted in an order of magnitude higher voltage response over neat PVDF for a given strain. When PENGs were mounted on a vacuum pump for transduction of mechanical vibrations into electrical energy, 2FNC/PVDF composite devices manifested similar to 3.8 times enhanced voltage output over neat PVDF and faster charging of a capacitor. The enhanced piezoelectric properties of PVDF/FNC nanocomposites could be attributed to the tailored interface between PVDF and nanocellulose and enhanced polarizability.
Keywords: Composite; Nanofiber; piezoelectric; pressure; Sensor; vibration

Piezoelectric energy harvesting from a ferroelectric hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] embedded in a polymer matrix - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2020)
Organic-inorganic hybrid ferroelectrics are an exciting class of molecular materials with promising applications in the area of energy and electronics. The synthesis, ferroelectric and piezoelectric energy harvesting behavior of a 3d metal ion-containing A(4)BX(6) type organic-inorganic hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] (1) is now presented. P-E hysteresis loop studies on 1 show a remnant ferroelectric polarization value of 18.71 mu C cm(-2), at room temperature. Composite thermoplastic polyurethane (TPU) devices with 5, 10, 15 and 20 wt % compositions of 1 were prepared and employed for piezoelectric energy harvesting studies. A maximum output voltage of 19.29 V and a calculated power density value of 2.51 mW cm(-3) were observed for the 15 wt % 1-TPU device. The capacitor charging experiments on the 15 wt % 1-TPU composite device shows an excellent energy storage performance with the highest stored energies and measured charges of 198.8 mu J and 600 mu C, respectively.
Keywords: energy conversion; mechanical properties; non-covalent interactions; organic-inorganic hybrid composites; Phosphorus

Flexible energy harvester from an organic ferroelectric ammonium salt - Gupta, Rishabh; Sahoo, Supriya; Deswal, Swati; Kothavade, Premkumar; Dixit, Prashant; Zareba, Jan K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry-An Asian Journal, 2021)
Organic ferroelectrics due to their low cost, easy preparation, light weight, high flexibility and phase stability are gaining tremendous attention in the field of portable electronics. In this work, we report the synthesis, structure and ferroelectric behavior of a two-component ammonium salt 2, containing a bulky [Bn(4-BrBn)NMe2](+) (Bn=benzyl and 4-BrBn=4-bromobenzyl) cation and tetrahedral (BF4)(-) anion. The structural analysis revealed the presence of rich non-classical C-H...F and C-H...Br interactions in this molecule that were quantified by Hirshfeld surface analysis. The polarization (P) vs. electric field (E) hysteresis loop measurements on 2 gave a remnant polarization (P-r) of 14.4 mu C cm(-2) at room temperature. Flexible polymer composites with various (5, 10, 15 and 20) weight percentages (wt%) of 2 in thermoplastic polyurethane (TPU) were prepared and tested for mechanical energy harvesting applications. A notable peak-to-peak output voltage of 20 V, maximum current density of 1.1 mu A cm(-2) and power density of 21.1 mu W cm(-2) were recorded for the 15 wt% 2-TPU composite device. Furthermore, the voltage output generated from this device was utilized to rapidly charge a 100 mu F capacitor, with stored energies and measured charges of 156 mu J and 121.6 mu C, respectively.
Keywords: Dielectric; energy harvesting; ferroelectricity; organic composites; piezoelectric

3D-printed polymer composite devices based on a ferroelectric chiral ammonium salt for high-performance piezoelectric energy harvesting - Sahoo, Supriya; Kothavade, Premkumar Anil; Naphade, Dipti R.; Torris, Arun; Praveenkumar, Balu; Zareba, Jan K.; Anthopoulos, Thomas D.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Materials Horizons, 2023)
Three-dimensional printing (3DP) is an emerging technology to fabricate complex architectures, necessary to realize state-of-the-art flexible and wearable electronic devices. In this regard, top-performing devices containing organic ferro- and piezoelectric compounds are desired to circumvent significant shortcomings of conventional piezoceramics, e.g. toxicity and high-temperature device processibility. Herein, we report on a 3D-printed composite of a chiral ferroelectric organic salt {[Me3CCH(Me)NH3][BF4]} (1) with a biodegradable polycaprolactone (PCL) polymer that serves as a highly efficient piezoelectric nanogenerator (PENG). The ferroelectric property of 1 originates from its polar tetragonal space group P4(2), verified by P-E loop measurements. The ferroelectric domain characteristics of 1 were further probed by piezoresponse force microscopy (PFM), which gave characteristic `butterfly' and hysteresis loops. The PFM amplitude vs. drive voltage measurements gave a relatively high magnitude of the converse piezoelectric coefficient for 1. PCL polymer composites with various weight percentages (wt%) of 1 were prepared and subjected to piezoelectric energy harvesting tests, which gave a maximum open-circuit voltage of 36.2 V and a power density of 48.1 mu W cm(-2) for the 10 wt% 1-PCL champion device. Furthermore, a gyroid-shaped 3D-printed 10 wt% 1-PCL composite was fabricated to test its practical utility, which gave an excellent output voltage of 41 V and a power density of 56.8 mu W cm(-2). These studies promise the potential of simple organic compounds for building PENG devices using advanced manufacturing technologies.

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus

Squarate-tethered enantiomeric Imido-Pd(II) cages for recognition and separation of chiral organic molecules - Jose, Cavya; Sarkar, Meghamala; Rajasekar, Prabhakaran; Tewari, Tanuja; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2023)
Chiral coordination cages have emerged as an efficient platform for enantioselective processes via host-guest interactions. Here, we report an enantiomeric pair of tetrahedral cages of formula [(Pd-3[PO(N(*CH(CH3)Ph)(3)])(4)(C4O4)(6)] supported by chiral tris(imido)phosphate trianions and squarate (C4O4)(2-) linkers. These cages exhibit unusual coordination isomerism for Pd(II)-linker bonds compared with the other Pd(II) cages of this family. Further, they were employed for the recognition and separation of small chiral molecules containing various functionalities. High enantioselectivities of 67 and 41 were found in the case of R-4-hydroxydihydrofuran-2(3H)-one and S-epichlorohydrin, recognized by the R-isomer of the cage. Chiral separation studies showed remarkable enantiomeric excess values of 93 and 85% for S-epichlorohydrin and R-4-benzyl-2-oxazolidinone, respectively, from their racemic mixtures. These studies showcase the potential of coordination cages for enantioselective applications.

Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity

Highly moisture-stable ferroelectric ammonium phosphate salt showing piezoelectric energy harvesting and rotation sensing applications - Kushwaha, Vikash; Prajesh, Neetu; Gopal, Animesh; Sahoo, Supriya; Deswal, Swati; Kirana, Antonysylvester; Shanmuganathan, Kadhiravan; Zareba, Jan K.; Boomishankar, Ramamoorthy (Journal of Materials Chemistry A, 2025)
Ferroelectric phosphate-based materials are known for their biocompatibility, dipole switching, and high thermal stability. In this context, we report a novel organic ferroelectric material, diisopropylammonium bis(4-nitrophenyl) phosphate (DIPABNPP), crystallizing in the monoclinic C2 space group. DIPABNPP exhibits a high second harmonic generation (SHG) efficiency 2.5 times higher than that of potassium dihydrogen phosphate (KDP). The ferroelectric nature of DIPABNPP was confirmed by the observation of a rectangular P-E hysteresis loop, which gave a saturated polarization value of 6.82 mu C cm-2. The ferroelectric polar domains of DIPABNPP, along with the bias-dependent amplitude butterfly and phase hysteresis loops, were visualized by piezoresponse force microscopy (PFM). Furthermore, the polydimethyl siloxane (PDMS) composites of DIPABNPP enabled the fabrication of humidity-resistant piezoelectric nanogenerators (PENGs) with energy harvesting and mechanical-electrical sensing capabilities. The top-performing 10 wt% DIPABNPP-PDMS device achieved a peak output voltage of 9.5 V and a charge storage efficiency of 81.8%, successfully powering 53 LEDs. Additionally, its rapid response time of 18.5 ms enables precise rotation sensing capabilities, suggesting potential applications in motion monitoring, such as revolution per minute (RPM) counting. We also present a unique and refined method for obtaining the output work efficiency (OWE) parameter, which quantifies the ratio of harvested electrical energy to the maximum elastic energy stored in the composite device, taking into consideration several key parameters during the PENG measurements. For the 10 wt% DIPABNPP-PDMS composite, an OWE of 13.1% was achieved, highlighting both its current performance and potential for optimization. This metric provides a standardized approach for evaluating PENGs, addressing a critical gap in assessing mechanical-to-electrical energy conversion efficiency.

Portal substituent modulations in chiral imido-Pd(II) cages for the enhanced separation of styrene oxide enantiomers - Jose, Cavya; Sarkar, Abhradeep; Khopade, Kishor V.; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2025)
Sensing and separation of enantiomers are crucial for the synthesis of biologically relevant compounds as well as for applications in catalysis and pharmaceutical development. Chiral coordination cages have gained significant attention as effective platforms for enantioselective processes through their well-defined, tunable cavities that facilitate host-guest interactions. In this study, we systematically explored the enantioselective binding and separation properties of two tetrahedral Pd(II) cages, 1-R and 2-R, with the molecular formula [Pd3(PO[N(RCH(CH3)Ph)3])4(C6O4X2)6] (X = Cl for 1-R, and X = F for 2-R). Their enantioselective abilities were investigated for small chiral molecules with diverse functional groups. Notably, the 2-R cage demonstrated a high enantioselectivity value of 88 for R-styrene oxide. Chiral separation experiments further revealed impressive enantiomeric excess (ee) values of 98% for R-styrene oxide from their racemic mixtures upon desorption from 2-R. The enhanced selectivity and separation efficiency were attributed to an optimal guest-to-cavity fit and the presence of multiple interaction sites within the host framework. Remarkably, portal substituent modulation in 2-R led to a 16-fold enhancement in enantioselective separation efficiency compared to 1-R, primarily due to improved portal dimensions, tighter molecular packing, and increased hydrogen bonding interactions. These findings highlight the potential of neutral chiral coordination cages for various enantioselective applications.

Steric hindrance modulated efficient thermally activated delayed fluorescence with non-linear optical, ferroelectric and piezoelectric properties - Dutta, Madhusudan; Chatterjee, Abhijit; Deka, Nilotpal; Tanwar, Riteeka; Mishra, Vishnu; Saha, Arindam; Mandal, Pankaj; Boomishankar, Ramamoorthy; Hazra, Partha (Chemical Science, 2025)
Multi-carbazole-based benzonitrile systems are efficient thermally activated delayed fluorescence (TADF) materials for organic light-emitting diodes (OLEDs). However, they suffer from low PLQY due to the large dihedral angle arising from steric crowding. Addressing this challenge, we demonstrate a potent strategy to engineer steric crowding in this work. To achieve our goal, we have designed three luminogens, namely, CzPHCN, tCzPHCN and Cz2CzPHCN based on phenanthrene-9,10-dicarbonitrile (PHCN), as an acceptor core to minimize the steric hindrance between the donor groups. Among the three luminogens, tCzPHCN exhibits a maximum PLQY of 86% and the highest RISC rate of 3.5 x 105 s-1, the underlying cause being the least dihedral angle of 45.72 degrees and suppressed intermolecular interaction due to the presence of the bulky tert-butyl group. Interestingly, our QM/MM calculations and experimental evidence suggest that the RISC process of both CzPHCN and tCzPHCN takes place via a hot exciton channel. Unlocking a new realm of applications, the unique non-centrosymmetric space group (Cmc21) of CzPHCN offers excellent SHG with a chi(2) value of 0.21 pm V-1 at 1320 nm. In addition to this, the molecule depicts good ferroelectric (PS = 0.32 mu C cm-2), piezoelectric energy harvesting (VOC = 2.8 V) and two-photon absorption properties.